Intrathecal administration of PD-1 inhibitor combined with pemetrexed for leptomeningeal metastases from breast cancer: a case report - Huang, Yushan; Yang, Guozi; Liu, Miaomiao; Tai, Panpan; Chen, Xiao; Liu, Min; Pan, Zhenyu (Frontiers in Immunology, 2025)
Leptomeningeal metastasis (LM) is a fatal complication of malignant tumors with limited treatment options. Finding more effective therapeutic strategies is of significant importance. This case reports an LM patient from breast cancer treated with intrathecal pemetrexed (15 mg) combined with PD-1 inhibitors (40 mg). The pemetrexed dosing regimen included an induction phase (twice weekly for 2 weeks), a consolidation phase (once weekly for 4 weeks), and a maintenance phase (once monthly). The PD-1 inhibitor dosing regimen included an induction phase (once every 2 weeks for 6 weeks) and a maintenance phase (once monthly). The patient showed good tolerance, with no severe adverse events observed, and achieved favorable therapeutic outcomes, including complete resolution of neurological symptoms, negative conversion of cerebrospinal fluid cytology, and significant reduction of imaging-detected lesions. This case provides a new approach to the treatment of LM, suggesting that intrathecal immunotherapy combined with intrathecal chemotherapy may be a safe and effective treatment option, offering valuable insights for future clinical applications.